Exploring the effect and mechanism of Shaoyao Gancao Decoction in the treatment of pain in Parkinson's disease using network pharmacology and molecular docking - Zhaohui Xu; Qing Zhao (IBRO Neuroscience Reports)
This study explores the potential effects and mechanisms of SGD in treating pain in PD based on network pharmacology and molecular docking technology.The chemical components in the aqueous extract from SGD were identified using GC-MS analysis. A prediction network describing the relationship between SGD and pain in PD was established based on information collected from multiple databases. Using Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Geomes (KEGG) pathway enrichment of key target genes in the DAVID6.8 database to obtain treatment target genes. To further investigate the molecular interactions, AutoDock Vina were employed to perform molecular docking and visualize the resulting outcomes. There were 206 targets obtained from the 105 active ingredients in Paeoniae Radix Alba and Radix Rhizoma Glycyrrhizae, and 5110 disease targets related to pain in PD were identified. GO enrichment analysis indicates that its Biologica Process (BP) involve response to lipopolysaccharide, response to metal ion. Cellular Component (CC) analysis suggests its primary impact on various membrane structural components. Molecular Function (MF) enrichment results primarily include ubiquitin-like protein ligase binding. KEGG pathway enrichment mainly encompasses MAPK, AGE-RAGE, IL-17, TNF, and Toll-like receptor signaling pathways. According to the results of molecular docking, the binding activity between core components and targets was marvelous (affinity < −5.0 kcal/mol). SGD has more advantages in the regulation of various types of pain in PD through multiple targets, which is worthy of further study.